Kinetic Study of Solvent Effect on the Acid CatalyzedSolvolysis of Methanoate Ester in Water-Dioxane Media - Singh, R.T.; Kiranmayee (Asian Journal of Chemistry, 2010)
The solvent effect of dioxane on the acid catalyzed solvolysis of ethyl-methanoate was studied by carrying out the hydrolysis of the ester in water-dioxane media of varying composition consisting of 0 to 80% dioxane (v/v) at different temperatures ranging from 20–40ºC. The specific rate constant values of the reaction were found to decrease with increasing concentration of dioxane in the reaction media. It was found that up to 1.5 molecules of water are associated with the activated complex The depletion observed in the values of isocomposition activation energy of the reaction shows that the transition is solvated and the initial state is desolvated with addition of dioxane in reaction media. From enhancement and depletion found, respectively in the values of ΔG* and in the values of both ΔH* and ΔS* (though up to different degrees), it is inferred that the reaction is entropy controlled and specific solvation is taking place in the waterdioxane media. From the values of isokinetic temperature, it may be concluded that water-dioxane reaction media does not check the reaction to follow Barclay-Butler rule.